2005
DOI: 10.1136/bjsm.2004.013151
|View full text |Cite
|
Sign up to set email alerts
|

Response of bone metabolism related hormones to a single session of strenuous exercise in active elderly subjects

Abstract: Objective: To evaluate the effect of strenuous exercise on bone metabolism and related hormones in elderly subjects. Methods: Twenty one active elderly subjects (11 men and 10 women; mean age 73.3 years) showing a mean theoretical Vo 2max of 151.4% participated. Concentrations of plasma ionised calcium (iCa), serum intact parathyroid hormone (iPTH), 25-hydroxyvitamin D (25(OH)D), and 1.25-dihydroxy-vitamin D3 (1.25(OH) 2 D3), as well as the bone biochemical markers type I collagen C-telopeptide for bone resorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 50 publications
5
33
2
1
Order By: Relevance
“…Increase in serum calcium has been observed following physical activities [23]. The absence of significant effects with jumping exercise alone on serum total calcium in the present study was consistent with Maimoun et al [24] which reported that a single session of strenuous exercise did not result in any significant change in serum total calcium.…”
Section: Discussionsupporting
confidence: 82%
“…Increase in serum calcium has been observed following physical activities [23]. The absence of significant effects with jumping exercise alone on serum total calcium in the present study was consistent with Maimoun et al [24] which reported that a single session of strenuous exercise did not result in any significant change in serum total calcium.…”
Section: Discussionsupporting
confidence: 82%
“…The change in osteocalcin after a single bout of exercise is unclear; it could decrease, 19 remain unchanged 27 or increase. 16 , 42 Conversely, the change in osteocalcin after a period of training is more obvious and tends to increase.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Maïmoun et al 34 involving a group of elderly people who performed strenuous physical activity, a change in bone metabolism was observed using distinct markers (blood calcium ions). Serum changes also occurred in the group analyzed in this study, demonstrating that physical exercise promoted beneficial changes in bone metabolism.…”
Section: Discussionmentioning
confidence: 99%